Falls resulting in mild traumatic brain injury and focal traumatic brain injury: a biomechanical analysis. Issue 3 (4th May 2018) - Post, Andrew; Kendall, Marshall; Cournoyer, Janie; Taylor, Karen; Hoshizaki, T. Blaine; Gilchrist, Michael D.; Brien, Susan; Cusimano, Michael D.; Marshall, Shawn
ABSTRACT: This research focuses on describing the differences between mild traumatic brain injury (mTBI) and focal traumatic brain injury (fTBI). The purpose of this research was to compare clinical mTBI and fTBI groups who incurred brain injury from falls to hard surfaces to identify clinical and biomechanical factors that may delineate between these two outcomes. Reconstructions of mTBI ( n = 11) and fTBI ( n = 20) cases that resulted from falls presented themselves at the hospital were conducted using computational and physical models. The cases were compared using peak and component dynamic response, brain injury criterion (BrIC), Gadd severity index and head injury criterion. Peak resultant rotational acceleration had the best percentage correct classification with 50% risk of severe TBI was found to be 21 krad/s 2 . The BrIC and component acceleration and rotational velocity of impact were also found to have significant predictions of risk between the two groups. This data provides information to improve risk thresholds for fTBI with application to helmet standards/development.